RETRACTED: Comparison of running time between C4.5 and k-nearest neighbor (k-NN) algorithm on deciding mainstay area clustering - Heru Ismanto; Retantyo Wardoyo (Universitas Ahmad Dahlan, 2016)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in International Journal of Advances in Intelligent Informatics to article entitled “Comparison of running time between C4.5 and k-nearest neighbor (k-NN) algorithm on deciding mainstay area clustering” Vol 2, No 1, pp. 1-6, March 2016, DOI: https://doi.org/10.26555/ijain.v2i1.49.This paper has been found to be in violation of the International Journal of Advances in Intelligent Informatics Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in IOSR Journal of Computer Engineering (IOSR - JCE), Vol. 18, No. 2 (Mar-April 2016), pp. 86-92, 2016, DOI: http://doi.org/10.9790/0661-1802048692, URL: http://www.iosrjournals.org/iosr-jce/papers/Vol18-issue2/Version-4/K1802048692.pdf entitled